Assessment of aquatic ecological health: A comparative study between cistern-made and ‘Natural’ earthen-made waterbody - Sukhendu Dey; Palas Samanta; Apurba Ratan Ghosh (Watershed Ecology and the Environment, 2023)
Ecological health of two waterbodies i.e., cistern-made and ‘natural’ earthen-made waterbody was compared in the present study based on temporal variations of physicochemical and biological parameters. Number of physicochemical parameters [transparency, temperature, pH, electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), dissolved oxygen (DO), total hardness (TH), total alkalinity (TA), biochemical oxygen demands (BOD), nitrate, phosphate and chlorophyll a (Chl a)], and biological parameters, e.g., zooplankton community and aquatic macrophytes were studied seasonally. Zooplankton communitiy comprised six arthropods and two rotifers. SIMPER analysis depicted that Moina sp., Daphnia sp., and Cyclops sp. were dominant species in cistern pond while Cyclops sp., Daphnia sp., Keratella sp. and Brachionus sp. were dominant in earthen natural pond. Abundance of species was highest in summer followed by post-rainy and winter in both the ponds while maximum abundance of zooplankton was recorded in summer. Species richness peaked in winter in natural pond, while in cistern pond species richness and diversity raised in summer. Multivariate analyses depicted significant temporal variation in zooplankton species in both the conditions. RELATE analysis revealed that temporal variation in species distribution and zooplankton community was significantly correlated with environmental parameters. Moreover, biological-environmental best matching (BIO-ENV) analyses indicated that water temperature, pH, TH and BOD (for cistern pond) and water temperature, EC and TSS (for earthen natural pond) were the main driving forces for temporal variations in species distribution and zooplankton community. Additionally, correlation analysis depicted that Moina sp., Daphnia sp., Diaptomus sp., Cyclops sp., Cypris sp., Bosmina sp., and species abundance was positively (significant) correlated with transparency, water temperature, and Chl a in natural pond. On the other hand, correlation analysis depicted that zooplankton species, species abundance, evenness and diversity were positively correlated with water temperature, DO, BOD and Chl a in cistern pond. Moreover, abundance of aquatic macrophytes were limited in three basic groups, namely free floating [(Lemna sp. (Major), Lemna sp. (Minor), Azolla sp., Pistia sp. and Eichhornia sp.], rooted submerged [Hydrilla sp., Ceratophyllum sp.] and rooted emerged [Nymphaes sp. and Ipomoea sp.]. Further, trophic state index (TSI) value revealed that both the ponds are hyper-eutrophic (‘natural’ waterbody > cistern waterbody) with a strong temporal variations. Therefore, these data could be used as water quality community-based bio-assessment tool as well as basis of water quality management plans to monitor the pollution level or conservation of aquatic ecology.